2021
DOI: 10.3390/genes12050647
|View full text |Cite
|
Sign up to set email alerts
|

MADS-Box Protein Complex VvAG2, VvSEP3 and VvAGL11 Regulates the Formation of Ovules in Vitis vinifera L. cv. ‘Xiangfei’

Abstract: The phenomenon of multi-carpel and multi-ovule exists in the grapevine cultivar ‘Xiangfei’, but the mechanism of ovule formation is seldom reported. In this study, we observed the ovule formation process by using ‘Xiangfei’ grapes. The role of the VvAG2 (VvAGAMOUS) gene in ovule formation was identified, and we explored the relationship between VvAG2, VvSEP3(VvMADS4) and VvAGL11(VvMADS5) proteins. The results showed that the ovule primordium appeared when the inflorescence length of ‘Xiangfei’ grapes were 4–5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Moreover, we evaluated the potential interaction between VvMADS39 and VvAG using bimolecular fluorescence complementation (BiFC). The interaction between VvSEP3 and VvAGL11, which has been previously tested (Wang et al., 2021), was used as the positive control. Moreover, two additional groups (VvMADS39–VvAGL11 and VvAG–VvAGL11) were used as the negative controls, because they did not show any interaction in yeast.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we evaluated the potential interaction between VvMADS39 and VvAG using bimolecular fluorescence complementation (BiFC). The interaction between VvSEP3 and VvAGL11, which has been previously tested (Wang et al., 2021), was used as the positive control. Moreover, two additional groups (VvMADS39–VvAGL11 and VvAG–VvAGL11) were used as the negative controls, because they did not show any interaction in yeast.…”
Section: Resultsmentioning
confidence: 99%
“…SEP3 is known to participate in several protein complexes as a bridge (Favaro et al., 2003). For instance, it can mediate complexation with different genes, such as STK , AG , SHP1/2 , and BELL , to regulate ovule development (Brambilla et al., 2007; Favaro et al., 2003; Wang et al., 2021). Although SEP3 is sufficient for normal ovule development, the fact that other genes in the SEP subfamily have been preserved during evolution suggests that they may have different functions and not be completely redundant (Mandel & Yanofsky, 1998; Savidge et al., 1995).…”
Section: Resultsmentioning
confidence: 99%
“…6d ). In our model, we speculate on a tetrameric organization of the complex involving only VviAGL11, but it should be taken into account the possibility of VviAGL11 interacting with other co-factors as previously proposed [ 11 , 24 ]. As shown in Figure 6 , in this latter hypothesis the combination of the WT AGL11 with the HYB or MUT protein may affect its ability to organize higher order complex and to exert its function on target genes.…”
Section: Discussionmentioning
confidence: 79%
“…VviAGL11 is a MIKC c -type gene, classified as a class D MADS-box gene, whose ability to establish higher-order complexes has already been demonstrated often [ 22 ], mediated by the presence of the SEP clade proteins [ 23 ]. For example, it has been reported that the grape MADS-box family transcription factor complexes VviAG2/VviSEP3 and VviAGL11/VviSEP3 form tetramers that may be involved in the formation of ovules before flowering and bloom [ 24 ]. On the other hand, we focused on the role of VviAGL11 on stenospermocarpy, studying a different developmental phase and this will likely involve different interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of studying the molecular mechanism of controlling seedless grapes found VvAGL11 transcription was essential for seed morphogenesis in grapevine during berry development [30]. On the formation process of ovule primordia of 'Xiangfei' grape, it was found that VvAG2 and VvAGL11 were involved in the formation of grape ovules [31]. In 'Muscadine' grape, VroAGL11 was found that the gene was most expressed in the berries with the highest seed content (weight) and almost not in seedless berries, indicating that VroAGL11 gene played an important role in controlling grape seed morphogenesis [32].…”
Section: Introductionmentioning
confidence: 99%